2007
DOI: 10.1111/j.1600-0404.2007.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen metabolism changes in patients with idiopathic normal pressure hydrocephalus before and after shunting operation

Abstract: The improvement of rCMRO(2) correlated with the response to VPS. Significant changes in rOEF might predict poor response to VPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…The gadobutrol propagated at the brain surface along large leptomeningeal arteries. The cerebral blood perfusion is reduced in iNPH as is the cerebral metabolism (Calcagni et al, ; Eide & Stanisic, ; Miyamoto, Tatsuzawa, Inoue, Imahori, & Mineura, ; Ziegelitz et al, ). Surgical diversion of CSF reduces the pulsatile and static ICP, likely facilitating the fluid and nutrient transfer at the capillary level as reflected by a long‐lasting clinical improvement (Eide & Sorteberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…The gadobutrol propagated at the brain surface along large leptomeningeal arteries. The cerebral blood perfusion is reduced in iNPH as is the cerebral metabolism (Calcagni et al, ; Eide & Stanisic, ; Miyamoto, Tatsuzawa, Inoue, Imahori, & Mineura, ; Ziegelitz et al, ). Surgical diversion of CSF reduces the pulsatile and static ICP, likely facilitating the fluid and nutrient transfer at the capillary level as reflected by a long‐lasting clinical improvement (Eide & Sorteberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, similar abnormalities and processes are implicated in hydrocephalus, stroke and traumatic brain injury, which may relate to shared pathogenic factors. Lastly, specific to hydrocephalus, shunting results in normalization of local CBF that has been linked to improved outcomes [200-202]; however, others have suggested that this may not account for clinical improvement seen in the long-term [193]. …”
Section: Cerebrovasculaturementioning
confidence: 99%
“…CBF and related parameters have been measured in human hydrocephalus using a variety of techniques including positron emission tomography, transcranial Doppler, and radionuclide angiography; most have demonstrated CBF reductions especially in white matter Shirane et al, 1992;Chang et al, 2009]. Improvement of blood flow after shunting may correlate with clinical improvement [Brooks et al, 1986;Nishimaki et al, 2004;Miyamoto et al, 2007]. Decreased blood flow is associated with local increases in glucose utilization in cats [Chumas et al, 1994], oxidative stress including lipid peroxidation and protein nitrosylation in H-Tx rats [Socci et al, 1999], and activation of calcium-dependent proteolytic enzymes that destroy axons in rats with kaolin-induced hydrocephalus [Del Bigio, 2000].…”
Section: Pathogenesis Of Brain Damage In Hydrocephalusmentioning
confidence: 99%